Humanity, Resilience, and Equity in Corporate Failure: A Literature Review on Developing Fairness Metrics for Inclusive Insolvency Systems - Grace Yulianti; Sigit Pramono Hadi (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2026)
Corporate insolvency regimes have long been designed around efficiency, creditor recovery, and procedural certainty, frequently marginalizing the human, social, and distributive consequences of corporate failure. This qualitative literature review seeks to reconceptualize insolvency as a multidimensional institutional process by integrating the principles of humanity, resilience, and equity, with the objective of developing fairness metrics for more inclusive insolvency systems. Drawing on interdisciplinary scholarship from insolvency law, corporate governance, economic sociology, and normative political theory, this study systematically synthesizes peer reviewed literature published between 2000 and 2024 using a structured qualitative thematic analysis. The review identifies three interrelated dimensions shaping inclusive insolvency outcomes. First, humanity-oriented approaches emphasize stakeholder vulnerability, dignity preservation, and procedural justice, particularly for employees, involuntary creditors, small suppliers, and local communities affected by corporate collapse. Second, resilience based perspectives frame insolvency not merely as an endpoint of failure but as an adaptive governance mechanism that enables organizational recovery, institutional learning, and broader systemic stability. Third, equity focused frameworks highlight the importance of proportional and context sensitive loss allocation, stakeholder participation, and intertemporal fairness in distributing the economic and social costs of insolvency. By integrating these dimensions, the study develops a conceptual framework of fairness metrics that extends beyond traditional efficiency-driven indicators, offering normative and analytical tools for evaluating insolvency systems in a more holistic manner. The findings contribute to insolvency scholarship by bridging fragmented theoretical strands and advancing a human-centered and resilience oriented understanding of corporate failure. The review further suggests that insolvency regimes embedding humanity, resilience, and equity are more likely to enhance institutional legitimacy, stakeholder trust, and long term economic sustainability, thereby providing a robust foundation for future empirical research and policy reform.